The Role of Gender Mainstreaming Policy and Teacher Belief: Strategies to Reduce the Impact of Stress on Special Needs Children's Mental Health - Mutiawati, Mutiawati; Syahputra, Andy; Nelly, Nelly (Mimbar Sekolah Dasar, 2025)
Children with special needs often experience stress due to the lack of inclusive environmental support, which can negatively impact their mental health and hinder the development of their full potential. This research discusses the role of education policy using the Integrated Education System (IES) as an effort to improve the quality of education in Aceh Besar district, Indonesia. The IES program organizes an education system by integrating national education with Acehnese cultural wisdom, namely, implementing a gender mainstreaming system and teachers' beliefs in the education patterns of children with special needs. The main objective of this study was to reduce the impact of stress on the mental health of children with special needs. This research employs a mixed-methods approach in a concurrent design structure, combining primary research using quantitative surveys with semi-structured qualitative interviews. The sample included principals and teachers from primary and secondary schools. Materials were delivered to students through instructional videos to eliminate gender-based discrimination and create an inclusive environment for students with disabilities. The findings show that the establishment of character-based Islamic education rooted in local excellence in the form of gender equality and teacher beliefs can reduce the impact of stress on the mental health of children with special needs. Ultimately, this research has the potential to contribute significantly to the development of a more equitable and inclusive education system for children with special needs. An interdisciplinary approach that integrates gender policy and teacher beliefs as two key factors in creating a supportive and inclusive learning environment.